A Geographic Information System for Managing and Mapping Irrigation Infrastructure - Insani, Rachmat Wahid Saleh; Agustini, Syarifah Putri (Politeknik Ganesha Medan, 2020)
Indonesia is one of the world's major agricultural nation which offers wide diversity of tropical products and agricultural commodities produced in substantial number of agricultural areas. Some of these areas are equipped with irrigation infrastructures which delivers water management throughout the land. Irrigation helps grow agricultural crops, maintain landscapes, and revegetation disturbed soils in dry areas. Water resources are finite while cyclic droughts on agricultural areas affecting the amount of water remains, thus creating unbalanced water demand and supply. Therefore, building an effective plan and management for irrigation infrastructure must be conducted using reliable information. The objective of this study is to develop a geographic information system to help managing and mapping process of irrigation infrastructure, such as flood gate and water ways. This system also helps to manage all the irrigation area and infrastructure data by providing geological information, search, and managing database function. We developed a web application for system interactivities. We also work together with Dinas Pekerjaan Umum dan Penataan Ruang of Kabupaten Kubu Raya, as they are managing nearest irrigation land which available to be inspected for research. The system has been tested in a real-life case study. As a result, the system enhances the efficient management of irrigation area and infrastructure data. Users stated that this geographic information system has many benefits to irrigation area management., i.e, ensuring data authorization with user information when data is recorded, real time image capture for each irrigation infrastructure, and digital maps to gain a wide overview of irrigation area information on Kabupaten Kubu Raya